Studi Eksperimental Pengaruh Sumber Kalor Terhadap Distribusi Temperatur dan Temperatur Pendidihan pada Tapering Heat Pipe - Sarip Sarip; Sudjito Sudjito; Lilis Yuliati; Moch. Agus Choiron (Jurnal Teknologi Terapan, 2016)
Heat source of the heat energy can affected of the temperature distribution and the boiling temperature of the tapering heat pipe located on the evaporator. The purpose of this study was conducted to determine the effect of heat source on the temperature distribution and boiling temperature that occur in the tapering heat pipe. In this study, used heat pipe tapered shape of the copper pipe diameter of 10 mm and 20 mm as evaporator as condenser with a length of 200 mm. Tapering heat pipe inside there is a wick mesh screen serves as the axis of the capillary to the return liquid / backflow of fluid from the condenser to the evaporator. The condenser ends mounted a valve to inject the working fluid into the tapering heat pipe. K-type thermocouple is integrated with NI-9211 module and c-DAQ 9271 to measure the temperature distribution along the tapering heat pipe with a heat source of DC power supply for (25, 30, 35, 40, 45, 50) Watt. The results showed that there was a difference of temperature distribution and boiling temperature caused by the variations heat source. Temperature of distribution and boiling temperature which tends to increase in value the greater the heat source, so it can be concluded that the heat source has an influence on the temperature distribution and the boiling temperature of the tapering heat pipe with 50 Watt heat source generates temperature distribution and boiling temperature stable.